2011
DOI: 10.5455/vetworld.4.260
|View full text |Cite
|
Sign up to set email alerts
|

Hematobiochemical changes of lead Poisoning and amelioration with Ocimum sanctum in wistar albino rats

Abstract: An experiment was carried out to study the hematobiochemical changes of chronic lead poisoning in adult male wistar albino rats for a period of twelve weeks. Adult 216 healthy rats were randomly divided into six groups viz. control (groupI), higher dose of lead acetate @60mgs/kg bwt (group II), Lower dose of lead acetate @ 30 mgs / kg bwt (group III), Higher dose of lead + Ocimum @ 400 mgs/ kg bwt (group IV), lower dose of lead + Ocimum @ 400 mgs/ kg bwt (group V), Ocimum control (group VI). All lead treated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 4 publications
3
12
0
Order By: Relevance
“…On contrary, Shrivastava (2011), Bhadauria (2012 showed that triglycerides levels were higher in the lead and aluminum treated group compared to the control group. Moreover, serum glucose level showed a significant decrease in lead treated groups in a dose dependent manner and not affected by aluminum treatment that agrees with Karamala et al (2011) andHassan et al (2008). This hypoglycemia might be due to the dysfunction of liver as the decrease in glucose-6-phosphatase activity indicates decrease degradation of glycogen, which may result in a subsequent decrease in blood glucose level (Gouda et al, 1985).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On contrary, Shrivastava (2011), Bhadauria (2012 showed that triglycerides levels were higher in the lead and aluminum treated group compared to the control group. Moreover, serum glucose level showed a significant decrease in lead treated groups in a dose dependent manner and not affected by aluminum treatment that agrees with Karamala et al (2011) andHassan et al (2008). This hypoglycemia might be due to the dysfunction of liver as the decrease in glucose-6-phosphatase activity indicates decrease degradation of glycogen, which may result in a subsequent decrease in blood glucose level (Gouda et al, 1985).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, Sadhana et al (2008) showed that aluminum generates oxidative stress in kidney which caused significantly rise in the activity of uric acid. On contrary to this, Karamala et al (2011), Shrivastava (2011 and Sadhana et al (2008) reported that lead acetate and aluminum administration resulted in an increase in serum Creatinine and urea.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 87%
“…Pb is a metallic element that emanates into the environment from various sources, including the industrial waste, combustion of fossil fuels, and the use of agrochemicals. Higher levels of Pb cause a variety of acute and chronic health problems, including cancer, kidney damage, heart problems, and even death [54].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to protecting against toxic chemicals, tulsi has also been shown to protect against the toxic effects of heavy metals such as lead, arsenic, cadmium, chromium and mercury[ 29 30 31 ] and the toxic effects of radiation. [ 32 33 34 35 ] Tulsi exerts its radio-protective effects by scavenging free radicals and reducing the oxidative cellular and chromosomal damage induced by radiation,[ 33 36 37 38 ] thereby reducing organ damage and enhancing postradiation survival in experimental animals.…”
Section: Introductionmentioning
confidence: 99%